2016
DOI: 10.1021/acs.iecr.5b04826
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of VX from Silicone: Characterization of Multicomponent Diffusion Effects

Abstract: A continuum model of the transport and reaction processes occurring during decontamination of the chemical warfare agent (CWA) [2-(diisopropylamino)ethyl]-O-ethyl methylphosphonothioate (VX) absorbed in a silicone elastomer using solutions of sodium hydroxide in water, methanol, and mixtures thereof is presented. This model is based on the Maxwell-Stefan formulation of multicomponent diffusion along with the Flory-Huggins model of thermodynamic equilibrium in the polymer. It was found that, as methanol from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…The inverse parameter estimation methodology employed for obtaining the values of c i sat and D i from the experimental vapor emission rate has been described in detail elsewhere. Briefly, initial guess values of c i sat and D i are used in one-dimensional finite difference models of the absorption and vapor emission processes to produce a model-predicted vapor emission rate. The emission rate predicted by the model, ṁ i mod , was computed from the molar flux of eq by multiplying by the constant material area of 0.32 cm 2 (based on the material diameter of 0.25 in., A = π d 2 /4) and the molecular mass of the chemical involved.…”
Section: Methodsmentioning
confidence: 99%
“…The inverse parameter estimation methodology employed for obtaining the values of c i sat and D i from the experimental vapor emission rate has been described in detail elsewhere. Briefly, initial guess values of c i sat and D i are used in one-dimensional finite difference models of the absorption and vapor emission processes to produce a model-predicted vapor emission rate. The emission rate predicted by the model, ṁ i mod , was computed from the molar flux of eq by multiplying by the constant material area of 0.32 cm 2 (based on the material diameter of 0.25 in., A = π d 2 /4) and the molecular mass of the chemical involved.…”
Section: Methodsmentioning
confidence: 99%
“…A failure to do so poses a continuing toxicological threat as winds, vehicles, and materials are moved outside the direct contamination zone. 2 Similar concerns often arise with a variety of organic liquids during accidental spills. A natural choice for efficient capture and removal of such chemicals is a highly swelling, absorbent polymer that can soak up and trap large volumes of organic liquids.…”
Section: Introductionmentioning
confidence: 90%
“…Rapid and efficient capture of such toxins is important in preventing lingering hazards due to absorption into surrounding porous materials including polymers, vehicle coatings, dust, and hazmat suits. A failure to do so poses a continuing toxicological threat as winds, vehicles, and materials are moved outside the direct contamination zone . Similar concerns often arise with a variety of organic liquids during accidental spills.…”
Section: Introductionmentioning
confidence: 98%
“…In certain cases, such as solvent extraction and decontamination of toxic chemicals from solid materials, the second component (termed solvent) is applied sequentially (after the initial contamination) to assist in the removal of the first component (termed penetrant). Previous research found that extraction of a penetrant (specifically, the nerve agent VX) from silicone elastomers with aqueous sodium hydroxide solutions was accelerated by the addition of the solvent methanol . Although this was attributed, in part, to an increased solubility of VX in more methanol-rich extraction solutions, the results also suggested that the associative interactions between the VX and the elastomer were disrupted by the presence of a secondary component (methanol) in the polymer, which accelerated the VX transport in the polymer. , For polyurethanes, it is hypothesized that these interactions are highly influenced by the functional groups on the polymer backbone that can participate in hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%